ChemInform Abstract: A New Strategy for the Synthesis of Dioxime Ether Derivatives with Nitromethylene Imidazolidine. Issue 29 (July 2015) - Zeng, Hui; Dong, Zhengjie; Chen, Xinfei; Shao, Xusheng; Xu, Xiaoyong; Li, Zhong
Abstract Unexpectedly, treatment of ketones (I) and (IV) with alkoxyamine hydrochlorides does not provide the target oxime ethers.